Incidence of Retained Placenta in Relation with Breed, Age, Parity and Body Condition Score of Dairy cows - Islam, MH; Sarder, MJU; Rahman, M; Kader, MA; Islam, MA (International Journal of Natural Sciences, 2012)
Retained placenta is an economically important reproductive disorder which occurs at the end of the reproductive cycle and has repercussions on the next. The study was conducted a total 1205 dairy cows from 9 upazila and 4 Metro Thana of Rajshahi during the period from July 2010 to June 2011. To evaluate the incidence of retained placenta in relation to breed, age, parity and body condition score of dairy cows. A questionnaire was prepared including information viz. name and address of farmer, breed, age; parity and body condition score for achievement of the study. The overall prevalence of retained placenta was 13.4%. The influencing factors including breed, age, parity, body condition score had significant effect (P<0.05) on retained placenta. The highest prevalence was 10.7%, 4.5%, 5.6% and 7.1% observed in cross-breed, > 3 years age, 1st parity and fair body condition group of cows, respectively. From this study, it might be concluded that local breed, ? 3 years but less than 5 years age group, 3rd parity had least risk for retained placenta. DOI: http://dx.doi.org/10.3329/ijns.v2i1.10878 International Journal of Natural Sciences (2012), 2(1): 15-20